2018
DOI: 10.1016/j.jcrs.2018.03.028
|View full text |Cite
|
Sign up to set email alerts
|

Comparing corneal higher-order aberrations in corneal wavefront-guided transepithelial photorefractive keratectomy versus small-incision lenticule extraction

Abstract: Small-incision lenticule extraction demonstrated that the induction of total HOAs was comparable to corneal wavefront-guided transepithelial PRK, accompanied by smaller spherical aberration induction and larger coma aberration induction. During small-incision lenticule extraction, surgeons should aim to obtain optimum centration for smaller induction of corneal HOAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 20 publications
3
28
0
1
Order By: Relevance
“…A recent study by Gyldenkerne et al [27] demonstrated that the spherical aberration did not change significantly at 3 months after SMILE surgery. Besides, Lee et al [28] compared the corneal aberrations between SMILE and transepithelial photorefractive keratectomy (PRK) after 6 months and found smaller spherical aberration and larger coma values in the SMILE group. e present study has several limitations.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Gyldenkerne et al [27] demonstrated that the spherical aberration did not change significantly at 3 months after SMILE surgery. Besides, Lee et al [28] compared the corneal aberrations between SMILE and transepithelial photorefractive keratectomy (PRK) after 6 months and found smaller spherical aberration and larger coma values in the SMILE group. e present study has several limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Wavefront analysis is an objective measurement of visual quality. The decline of visual quality is related to the aberrations [13]. Aberrations can be divided into low-order aberrations (sphere and cylinder) and high-order aberrations.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that the results of this study can only be applied to situations where our cornea model and the refractive surgery technique (LASIK) were used. New surgical techniques, as SMILE and FLEx, can induce smaller spherical aberration changes than LASIK [44] so the results of this study could not be applied to them. Moreover, regarding the post-LASIK model cornea used in this work, it is important to remark that despite the fact than it corresponds to an early surgery stage (1 to 3 months after surgery), it is not very risky to assume, attending to current evidence as Vega-Estrada et al [45], that it can also be suitable for a more advanced state previous to an IOL replacement intervention.…”
Section: Plos Onementioning
confidence: 99%